Studium v projektových skupinách - Baťa, Robert (Univerzita Pardubice, 2002)
The practical work combines elements of practice's training and academic courses. The idea is not depend always from the teacher, but more from the students. This method should be better for the students because that will help them to remind more the materials and increase the knowledge and ability to resolve new problems. Participation is a most, proactive behavior by the student, presentations, group work, case studies and approbation of the test.
Keywords: studium; pracovní skupiny; Spolupráce; komunikace ve výchově a vzdělávání; projekty